(untitled) (Revista de Administração, 2016)
In this article, we review literature on socioemotional wealth. We explain how the concept of socioemotional wealth builds on previous family firm research showing that family-owners derive utility from the nonfinancial aspects of their firm. We also discuss how family firms' need for socioemotional wealth preservation explains behavioral differences between family and nonfamily firms in managerial decision making. Finally, we discuss the current state of socioemotional wealth research and propose potential directions for future research.